Mechanism Of The Free Charge Carrier Generation In The Dielectric Breakdown - Ranom, Rahifa; Rahim, N. A. A.; Zainuddin, Hidayat (Institute of Physics Publishing, 2018)
Many studies have been conducted to investigate the effect of environmental,mechanical and electrical stresses on insulator.However,studies on physical process of discharge phenomenon,leading to the breakdown of the insulator surface are lacking and difficult to comprehend.Therefore,this paper analysed charge carrier generation mechanism that can cause free charge carrier generation,leading toward surface discharge development. Besides,this paper developed a model of surface discharge based on the charge generation mechanism on the outdoor insulator.Nernst’s Planck theory was used in order to model the behaviour of the charge carriers while Poisson’s equation was used to determine the distribution of electric field on insulator surface.In the modelling of surface discharge on the outdoor insulator,electric field dependent molecular ionization was used as the charge generation mechanism.A mathematical model of the surface discharge was solved using method of line technique (MOL).The result from the mathematical model showed that the behaviour of net space charge density was correlated with the electric field distribution.